MENGUNGKAP MAKNA SINDIRAN PERUMPAMAAN YOTAM TAFSIRN HISTORIS HAKIM-HAKIM 9:7–15 DALAM KONTEKS KEPEMIMPINAN ABIMELEKH - Abigael Stevani Putri; Milka; Tasya Patrica (Adiba Aisha Amira, 2026)
This study aims to uncover the satirical meaning of Jotham's parable (Judges 9:7–15) through a historical interpretation approach in the context of Abimelech's leadership. The method used is qualitative with a literature review (biblical exegesis), integrating historical-critical and thematic analysis of the text and related literature. The results show that Jotham's parable is a form of socio-political criticism conveyed symbolically through the fable of the trees. The olive, fig, and vine trees symbolize ideal, productive leadership oriented toward the welfare of the community, while the thornbush represents Abimelech's selfish, unproductive, and destructive leadership. The satire in the text is conveyed indirectly through figurative language, irony, and repetitive structures that reinforce its rhetorical message. In a historical context, this parable emerged as a response to Abimelech's power, which was obtained through violence and manipulation, thus lacking moral and theological legitimacy. These findings emphasize that leadership not rooted in divine values ​​and social responsibility will lead to destruction. Thus, the parable of Jotham not only has historical significance, but also theological relevance as a critique of deviant leadership and as a basis for reflection for contemporary Christian leadership.